Women waiting to welcome the palki procession - Mumbai Archive Project Team (Jio Institute, 2024)
Women wait in anticipation outside their homes with an aarti thali in hand to welcome the palki procession. The thali (plate) usually contains a diya (oil lamp), incense sticks, marigold flowers, and raw rice grains. A small bell is rung during aarti to invoke the divine and ward off negative energies.